CECs and IL-8 Have Prognostic and Predictive Utility in Patients with Recurrent Platinum-Sensitive Ovarian Cancer: Biomarker Correlates from the Randomized Phase-2 Trial of Olaparib and Cediranib Compared with Olaparib in Recurrent Platinum-Sensitive Ovarian Cancer - Lee, Jung-Min; Trepel, Jane B.; Choyke, Peter; Cao, Liang; Sissung, Tristan; Houston, Nicole; Yu, Minshu; Figg, William D.; Turkbey, Ismail Baris; Steinberg, Seth M.; Lee, Min-Jung; Ivy, S. Percy; et al. (Frontiers in Oncology, 2015)
Objective: Olaparib (O), a PARP inhibitor, and cediranib (C), a VEGFR1-3 inhibitor together had greater activity than O alone in women with recurrent platinum-sensitive ovarian cancer (OvCa). The objective of this study is to identify potential lead biomarker candidates for response to O+C in the setting of a multi-institutional phase II study of O with and without C in recurrent platinum-sensitive OvCa. Methods: A self-selected group of patients participated in a prospectively planned exploratory biomarker substudy of the randomized phase II study of O v. O+C. Whole blood for peripheral blood mononuclear cell (PBMC) and plasma isolation was collected prior to and on day 3 of treatment. Quantitation of circulating endothelial cells (CEC), IL-6, IL-8, VEGF, and soluble VEGFR-2 plasma concentrations, and polyADPribose (PAR) incorporation were performed. SNP analysis of XRCC1 280H, R194W, and Q399R was done. Dynamic contrast enhanced-magnetic resonance imaging (DCE-MRI) was performed at baseline and day 3 of treatment. Parameter changes were compared between the two arms using an exact Wilcoxon rank sum test. Kaplan-Meier and log-rank tests were used to examine survival outcome. Results: 13 patients elected to participate in the translational substudy, 7 patients on O and 6 patients on O+C. Patients on O+C had a greater decrease in IL-8 concentration and larger CEC fold-increase compared with those on O alone (p=0.026, p=0.032). The fold increase in CEC on day 3 was associated with duration of PFS (R2=0.77, 95% CI 0.55-0.97, p<0.001). IL-8 post-pretreatment changes correlate with PFS (p=0.028). XRCC1 DNA polymorphisms were not related to PFS. All patients had reduction in PAR incorporation, and all except one had reduction in vascular flow on DCE-MRI. Conclusions: Our exploratory correlative studies indicate CEC and IL-8 changes may be predictive for response to O+C and prognostic in recurrent platinum-sensitive OvCa, requiring prospective validation.